Theoretical Basis for Training Future Education Managers to Form a Professional Image - Denys Besedin (Pedagogical Discourse, 2025)
The article highlights the theoretical foundations of training future education managers in the aspect of image formation. Given that the professional image of the head of an educational institution is not only his or her personal characteristic, but also an essential factor in the strategic development of the institution, there is a growing need for the purposeful formation of image culture as a component of professional training.The purpose of the article is to reveal the theoretical foundations of training future education managers to form a professional image as a component of their professional identity and managerial culture. To achieve this goal, the article analyzes scientific and theoretical sources on the formation of the image of a leader in the educational context, clarifies the essence of the concept of «professional image of an education manager», systematizes its characteristics and functions, and substantiates the principles and content of training students for image activities. In the course of the study, the methods of theoretical analysis, specification, system analysis and generalization were applied, which allowed to organize existing scientific approaches and to highlight the conceptual provisions for organizing pedagogical support of the image creation process. The author’s own definition of the concept of «professional image of an education manager is proposed and it is proved that the professional image of an education manager can be interpreted as an integral, systemic phenomenon that combines personal qualities, communication skills, managerial competencies and socio-psychological attitudes, ensuring the effectiveness of managerial interaction. It is proved that the image is not a purely spontaneous formation, but is subject to purposeful formation through pedagogical technologies that take into account both external expectations and the internal professional identity of the future leader. The functional characteristics of the image – flexibility, integrity, dependence on public expectations, etc. – are systematized and their role in achieving professional performance is revealed. It is substantiated that the training of future managers for image activity should be based on the principles of humanistic orientation, professional relevance, reflexivity, taking into account the context of the functioning of the educational institution, the unity of personal development and professional training. The results of the study confirm the expediency of forming image competence as a key element of the professional skills of a future manager in education.